The talented Mrs. Mandelbaum : the rise and fall of an American organized-crime boss - Fox, Margalit (Random House, 2024)
"In 1850, Fredericka Mandelbaum emigrated to New York from Germany and worked as a rag peddler on the streets of the Lower East Side. By the 1870s she was a widow with four children, a popular society hostess, and a philanthropist. What enabled a woman on the margins of nineteenth-century American life to ascend from tenement poverty to immense wealth? In the intervening years, Mrs. Mandelbaum had become the country's most notorious "fence"-a receiver of stolen goods and a successful criminal mastermind. By the mid-1880s as much as $10 million worth of purloined property (the equivalent of nearly $300 million in today's money) had passed through her little haberdashery shop. She planned, financed, and profited from robberies of cash, gold, and diamonds throughout New York and beyond. But she wasn't just a successful crook, she was a visionary. Called "the nucleus and center of the whole organization of crime in New York City" by the New York Times, Mandelbaum was the first person in American history to systemize formerly scattershot property crime enterprises. Handpicking a cadre of New York's foremost bank robbers, housebreakers, and shoplifters and bribing a corresponding group of the city's police and politicians, she handled logistics and organized supply chains--turning theft into a proper, scaled business"--